Cechy polskiego rynku krótkoterminowych papierów dłużnych w Polsce - wyniki badań ankietowych - Pauka, Marek (Characteristic of the Commercial Paper Market in Poland - the Survey Results, 2007)
On the private short-term debt securities market in Poland the problem is a downward tendency in the last years. The author conducted a survey among issue agents on the market to identify factors that influence the market. The paper presents chosen results of the survey.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 401-409